2017
DOI: 10.1097/hjh.0000000000001434
|View full text |Cite
|
Sign up to set email alerts
|

Role of the sympathetic nervous system in regulation of the sodium glucose cotransporter 2

Abstract: Our in-vitro and in-vivo studies provide first evidence for an important cross-talk between the SNS and SGLT2 regulation that may not only account for SNS-induced alterations of glucose metabolism but potentially contribute to cardiovascular and renal protection observed with SGLT2 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 39 publications
6
122
0
4
Order By: Relevance
“…Conversely, we found no signi cant difference in LP as an indicator of depolarization or TWA as an indicator of repolarization abnormality. Although experimental data and clinical case reports have suggested that SGLT2 inhibitors improved cardiac sympathetic hyperactivity [16,17], the present study, to the best of our knowledge, is the rst trial to provide randomized clinical data demonstrating that empagli ozin improved both the cardiac sympathetic and parasympathetic activities in humans. The evidence connecting the autonomic nervous system to life-threatening arrhythmias and cardiovascular mortality is well established [18][19][20].…”
Section: Discussionmentioning
confidence: 76%
“…Conversely, we found no signi cant difference in LP as an indicator of depolarization or TWA as an indicator of repolarization abnormality. Although experimental data and clinical case reports have suggested that SGLT2 inhibitors improved cardiac sympathetic hyperactivity [16,17], the present study, to the best of our knowledge, is the rst trial to provide randomized clinical data demonstrating that empagli ozin improved both the cardiac sympathetic and parasympathetic activities in humans. The evidence connecting the autonomic nervous system to life-threatening arrhythmias and cardiovascular mortality is well established [18][19][20].…”
Section: Discussionmentioning
confidence: 76%
“…Adipokines such as tumour necrosis factor-α and interleukin 6 (IL-6) were found to upregulate SGLT2 in vitro 41 , and increased adiponectin was shown to cause activation of PPARδ in the adipose tissue and reduce renal SGLT2 35 . Recent evidence showed potential cross-talk between the sympathetic nervous system and SGLT2 regulation 42 while sex and species differences appeared to be influencing SGLT2 expression in rodents 43 . At the transcriptional level, hepatocyte nuclear factor 1 alpha (HNF1α) is known to bind to the SGLT2 promoter in the kidney, and had been considered a vital transcription factor for SGLT2 expression since HNF1α -null mice have reduced SGLT2 transcript levels in tubular cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Leptin can promote sodium retention by increasing sympathetic nerve traffic to the kidneys, but SGLT2 inhibitors decrease this traffic to the periphery, explaining the lack of a reflex sympathetic nerve response to their natriuretic effects . Furthermore, leptin‐mediated neurohormonal activation causes upregulation of SGLT2 in the renal tubules, potentially explaining why the renal response to inhibitors of the renin‐angiotensin system parallels that seen with SGLT2 inhibitors in individual patients . In addition, SGLT2 suppression leads to decreases in serum aldosterone (thus opposing the actions of leptin), despite the decrease in plasma volume.…”
Section: Potential Role Of Sglt2 Antagonists As Antagonists Of Leptinmentioning
confidence: 99%
“…Leptin decreases the expression of SGLT1 in the intestinal epithelium, thus adaptively attenuating the absorption of glucose into the bloodstream . In contrast, leptin‐mediated activation of the sympathetic nerve system and renin‐angiotensin system causes upregulation of SGLT2 in the renal tubules, thus enhancing the clearance of glucose from the bloodstream.…”
Section: Is the Relationship Between Sglt2 Inhibitors And Leptin A Comentioning
confidence: 99%